The Impact of Endodontic Status on Quality of Life - Petra Dijanić; Ana Ivanišević; Silvana Jukić Krmek; Jelena Perica Pavešić; Zoran Karlović; Jurica Matijević (Acta Clinica Croatica)
The influence of endodontic status on quality of life has not been fully clarified. The aim of this study was to quantify the effect of endodontic status on everyday functioning using the psychometric instrument Oral Impacts on Daily Performances (OIDP) and to correlate endodontic status with quality of life using the OIDP questionnaire. A total of 600 participants were referred to dental radiography for digital orthopantomograms and asked to fill out the OIDP questionnaire. Digital orthopantomograms were analyzed and compared with OIDP results. The correlation between endodontic status and quality of life was tested. The statistical analysis consisted of descriptive statistics, non-parametric statistics, hierarchical multiple regression analysis by enter method, and correlation analysis. The results showed that quality of life was significantly affected by tooth loss (p<0.05). Endodontic treatment on canines and incisors positively correlated with higher OIDP scores, indicating an effect on quality of life (p<0.05). In conclusion, the correlations between variables describing the endodontic status and the quantitative results of the OIDP questionnaire indicate a measurable effect of endodontic disease/health on everyday functioning.